FINANCING ENERGY TRANSITION: THE NUTS AND BOLTS OF TAX EQUITY FINANCING IN THE U.S. RENEWABLE ENERGY LANDSCAPE AND ITS FUTURE OUTLOOK - Sim, Stephen (Jurnal Paradigma Hukum Pembangunan, 2025)
Financing remains one of the biggest hurdles in the United States transition to renewable energy, especially as clean energy projects often carry higher upfront costs than fossil fuels. To close this gap, developers rely heavily on government incentives like the Investment Tax Credit (ITC) and Production Tax Credit (PTC), often through tax equity financing structures. This paper explores how the Inflation Reduction Act of 2022 has reshaped the renewable energy financing landscape, expanding access to tax credits, introducing transferability, and allowing more flexible funding models. It focuses on how these changes are impacting common structures like the partnership flip and giving rise to new tools, such as tax credit transfer. The paper also looks ahead, considering how shifts in political leadership influence the future of these incentives, and what that means for investors, developers, and the broader clean energy market.